Analysis of the rumen bacterial diversity of goats during shift from forage to concentrate diet - Grilli, Diego Javier; Fliegerová, Kateřina; Kopečný, Jan; Lama, Sebastián Paez; Egea, Vanina; Sohaefer, Noelia; Pereyra, Celia; Ruiz, María Soledad; Sosa, Miguel Angel; Arenas, Graciela Nora; Mrázek, Jakub (Anaerobe, 2016)
High-grain feeding used in the animal production is known to affect the host rumen bacterial community, but our understanding of consequent changes in goats is limited. This study was therefore aimed to evaluate bacterial population dynamics during 20 days adaptation of 4 ruminally cannulated goats to the high-grain diet (grain: hay - ratio of 40:60). The dietary transition of goats from the forage to the high-grain-diet resulted in the significant decrease of rumen fluid pH, which was however still higher than value established for acute or subacute ruminal acidosis was not diagnosed in studied animals. DGGE analysis demonstrated distinct ruminal microbial populations in hay-fed and grain-fed animals, but the substantial animal-to-animal variation were detected. Quantitative PCR showed for grain-fed animals significantly higher number of bacteria belonging to Clostridium leptum group at 10 days after the incorporation of corn into the diet and significantly lower concentration of bacteria belonging to Actinobacteria phylum at the day 20 after dietary change. Taxonomic distribution analysed by NGS at day 20 revealed the similar prevalence of the phyla Firmicutes and Bacteroidetes in all goats, significantly higher presence of the unclassified genus of groups of Bacteroidales and Ruminococcaceae in grain-fed animals and significantly higher presence the genus Prevotella and Butyrivibrio in the forage-fed animals. The three different culture-independent methods used in this study show that high proportion of concentrate in goat diet does not induce any serious disturbance of their rumen ecosystem and indicate the good adaptive response of caprine ruminal bacteria to incorporation of corn into the diet.
Keywords: Animals; Clostridium; Rumen; Goats; Hydrogen-Ion Concentration; Gastric Fistula; Gastrointestinal Microbiome; Animal Feed; Butyrivibrio; Bacteroidetes; píštěl žaludku; bachor; fermentace; Prevotella; kukuřice setá; Poaceae; Phylogeny; Firmicutes; kozy; fyziologie výživy zvířat; střevní mikroflóra; lipnicovité; Zea mays; Fermentation; Animal Nutritional Physiological Phenomena; Sequence Analysis, DNA; krmivo pro zvířata; Actinobacteria; zvířata; sekvenční analýza DNA; fylogeneze; koncentrace vodíkových iontů; Ruminococcus